THE EFFECT OF WORKLOAD AND JOB STRESS ON EMPLOYEE TURNOVER INTENTION - Arnas, Yenni; Wibowo, Sandi Nasrudin; Maemunah, Siti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to determine the Effect of Workload and Work Stress on Turnover Intention at PT. Sumber Alfaria Trijaya Tbk Plumbon Branch used in sampling is using probability sampling where this sampling technique provides equal opportunities for each element (member) of the population to be selected as a member of the sample. Methods in data collection using a questionnaire, while the analysis technique used is multiple linear regression. The results of this study indicate that there is a positive and significant influence between workload on turnover intention seen from tcount>ttable, namely 2.678 > 1.996. And there is the effect of work stress which has a positive and significant effect on turnover intention. It can be seen from tcount > ttable, namely 2,796 > 1,996.